Evaluation of the Evan’s and Bicaudate index for South Karnataka Population using computed tomography - Praveen Basavaraj Kumbar; Anil Kumar Sakalecha; Chaithanya A; Rajeswari G; Revanth RB; Jayendra Mannan (Asian Journal of Medical Sciences, 2023)
Background: Radiological markers that are useful in the diagnosis of normal pressure hydrocephalus include the Bicaudate index (BCI) and the Evans index (EI), which are practical indicators of ventricular volume. Worldwide, variation exists in normative studies for both these indices. The majority of research for EI and BCI is based on data from the Western population. The study has been performed on the South Karnataka population. Aims and Objectives: This study’s goal is to derive age and gender specific cutoff values on normative data of Evans and BCI. Materials and Methods: This was a prospective and observational study.Patients referred to “RL Jalappa Hospital” for computed tomography (CT) scan of the brain who meet the inclusion criteria will be included in this study. CT brain of all the patients will be performed in Siemens Somatom emotion 16 slice CT scanner. Ninety-seven were selected for this study, and EI and BCI were calculated for them. Results: The mean value of EI and BCI in our study was 0.26±0.02 and 0.1167±0.02, respectively. The difference in EI and BCI between males and females shown significant statistical difference between males and females but the values increased as increase in age. Conclusion: Our study for South Indian population concludes that EI and BCI have a significant statistical difference between males and females. Both EI and BCI values increase with age. Hence cutoff values of EI and BCI index according to age and gender are important for evaluation of hydrocephalus.